Analisis Finansial Usaha Pembesaran Ikan Nila dalam Keramba “H. Jam’an” Di Desa Sungai Hanyar Kecamatan Banua Lawas Kabupaten Tabalong - Miranda Romaully Br. Sitanggang; Mahdalena Mahdalena; Norhasanah Norhasanah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2015)
This study aims to (i) find out the magnitude of the Net Present Value (NPV) and Internal Rate of Return (IRR) efforts to enlarge tilapia in cages in Sungai Hanyar Village (ii) to know the Pay Back Prize to restore business capital enlargement of tilapia in cages (iv) knowing the break-even point (Break Event Point) in an effort to enlarge tilapia in cages. The method used is descriptive method. The research design is case study design and field research. Analysis of the data used is financial and to make a feasibility study is financial analysis and to make a case study of field research. Data analysis using NPV, IRR <, and PBP. The total cost of maintaining tilapia is Rp. 55,210,012, - per year, while income is Rp. 153,250,000 per year and income in the tilapia fish maintenance business Rp. 101,836,000 million, - per year. In the maintenance business of tilapia H. Jam'an in Sungai Hanyar Banua Lawas Tabalong Regency based on an analysis of the investment feasibility of Net Net Value Value (NPV) of Rp. 220,353,136 is known, - The results of the study show NPV> 0, meaning that the effort to enlarge H.jam'an indigo is feasible / continued. Based on the Retrun calculation method internally produces 87% and the social opportunity cost of capital (SOCC) of 18% means IRR> SOCC, thus the business of enlarging H.Jam'an tilapia in Sungai Hanyar Village, Banua Lawas District, Tabalong Regency is feasible to be cultivated / next. The results of the feasibility analysis based on the payback period investment (PBP) in the maintenance business of H. Jam'an tilapia in Sungai Hanyar Banua Lawas, District of Tabalong 1 year 11 months 28 days have received a return on investment.